2015
DOI: 10.1111/1462-2920.13046
|View full text |Cite
|
Sign up to set email alerts
|

Age polyethism drives community structure of the bacterial gut microbiota in the fungus‐cultivating termite Odontotermes formosanus

Abstract: Fungus-cultivating termites (Macrotermitinae) possess an elaborate strategy of lignocellulose digestion. It involves a lignocellulose-degrading fungal symbiont (genus Termitomyces), a diverse gut microbiota and a characteristic labour division in food processing. In this study, using pyrotag sequencing and electron microscopy, we analysed the bacterial microbiota in the hindgut of Odontotermes formosanus and its fungus comb to investigate the spatial organization, establishment and temporal succession of the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
41
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 55 publications
5
41
0
Order By: Relevance
“…Lachnospiraceae are more abundant in Odontotermes formosanus young termites feeding mainly on 329 fungal nodules or degrading non-cellulosic plant oligosaccharides (Li et al, 2016) and contributing 330 to lignin depolymerisation (Li et al, 2017). Similarly, Alistipes III (OTU8, Figure 1B; 331 Supplementary Table S2) was significantly more abundant in Odontotermes soldier guts compared 332 to worker guts ( Figure 2I, J), consistent with the sequencing results ( Figure 1B, Supplementary 333 Table S12).…”
Section: Sequencing and Bacterial Identification 240supporting
confidence: 70%
“…Lachnospiraceae are more abundant in Odontotermes formosanus young termites feeding mainly on 329 fungal nodules or degrading non-cellulosic plant oligosaccharides (Li et al, 2016) and contributing 330 to lignin depolymerisation (Li et al, 2017). Similarly, Alistipes III (OTU8, Figure 1B; 331 Supplementary Table S2) was significantly more abundant in Odontotermes soldier guts compared 332 to worker guts ( Figure 2I, J), consistent with the sequencing results ( Figure 1B, Supplementary 333 Table S12).…”
Section: Sequencing and Bacterial Identification 240supporting
confidence: 70%
“…Apparently, the enzymes in young worker termite guts work in conjunction with intestinal microbiota to depolymerize lignin. Moreover, the comparative studies of fresh and middle-aged fungus comb showed that continuous cleavage of lignin sidechains is occurring throughout this process, but with no further depletion in the mature fungus comb, implying the bacterial lineages in the fresh comb derived from the feces of young workers may have similar lignin-degrading abilities to those in the gut, and thus subsequently contribute to the complete lignin depolymerization (39,40).…”
Section: Original Poplar Woodmentioning
confidence: 97%
“…microbiome-including its dense Termitomyces mycelial mass, replete with laccases, and harboring unique bacterial lineageshas the ability to extensively mineralize aromatics (39,40).…”
Section: Original Poplar Woodmentioning
confidence: 99%
“…Microbial communities differ between hosts that specialize on different substrates (Muegge et al , 2011) and changes in these communities and their functional capacity are integral to their hosts’ transition to utilizing novel substrates (Hammer and Bowers, 2015; Delsuc et al , 2013; Li et al , 2015; Kohl et al , 2014; 2016). This phenomenon is not isolated to herbivores – in many systems, gut microbial communities are influence by the inputs of their hosts (Goffredi et al , 2005; Roman et al , 2015; Muegge et al , 2011; Youngblut et al , 2019; Wang et al , 2011; Li et al , 2016).…”
Section: Introductionmentioning
confidence: 99%